Chatbot-Based Application Development and Implementation as an Autonomous Language Learning Medium - Nuria Haristiani; Mumu Muhammad Rifai (Universitas Pendidikan Indonesia, 2021)
Autonomous learning has an important role in online learning because teachers cannot directly supervise the student learning process, which makes students themselves responsible for their learning. As an attempt to provide teachers with an alternative autonomous learning medium, this study aimed to use a chatbot-based Japanese grammar learning application namely Gengobot as an autonomous Japanese learning medium. This study applied Analysis, Design, Development, Implementation, and Evaluation (ADDIE) instructional design model. The data of this research was collected using a pre-experimental method and distributed a Likert scale questionnaire to 50 Japanese language learners with Japanese language levels equivalent to or less than JLPT level N3. The results showed that Gengobot as a chatbot-based Japanese grammar learning medium is an interesting and innovative medium to support Japanese autonomous learning because learners can decide how they learn using this application to improve their Japanese grammar skills. In addition, Gengobot is a chatbot-based learning medium that is more interactive than other Mobile-based media, which makes learners more interested in using Gengobot as a Japanese grammar learning medium. However, Gengobot still needs further development such as adding advanced grammar content (N2 and N1), adding Japanese pronunciation features (audio), etc.